Brand-Generated Content, User-Generated Content, and Purchase Intention: The Mediating Role of Social Media Engagement Among Generation Z TikTok Users - Neva Aliya Sagita; Elvira Azis (Politeknik Siber Cerdika Internasional, 2026)
Background: Social media has become a major communication channel for brands, especially in reaching Generation Z, who are highly active on digital platforms. TikTok enables both brands and users to create content that shapes consumer perceptions and purchase decisions. In the skincare industry, Skintific is frequently discussed through Brand-Generated Content (BGC) and User-Generated Content (UGC), making it important to examine their influence on Generation Z consumers in Bandung. Objective: This study aims to analyze the influence of BGC and UGC on purchase intention and examine the mediating role of social media engagement among Generation Z TikTok users. Methods: This study used a quantitative survey approach involving 400 Generation Z respondents in Bandung who actively use TikTok. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships among BGC, UGC, social media engagement, and purchase intention. Results: The findings show that BGC positively and significantly influenced purchase intention (β = 0.372, p < 0.001), while UGC also had a positive and significant effect (β = 0.316, p < 0.001). Social media engagement partially mediated both relationships, with an R² value of 0.737 for purchase intention. BGC showed the strongest effect on social media engagement (β = 0.510). Conclusion: BGC and UGC significantly influence purchase intention directly and indirectly through social media engagement. These findings highlight the importance of interactive, authentic, and engaging TikTok content in increasing Skintific purchase intention among Generation Z consumers.